Bugden, Roberta. Interview about growing up in St. John's - Barrett, Terra (2017)
Interview with Roberta Bugden about growing up in St. John's. Includes memories of family history including mother's memories of the Great Fire of 1892 and the Ross family farm, Water Street and the St. John's Harbour, school, children's games, Christmas, and changes to St. John's over time.